Possibilities of Energy Harvesting from the Suspension System of the Internal Combustion Engine in a Vehicle - Jacek Caban; Grzegorz Litak; Bartłomiej Ambrożkiewicz; Leszek Gardyński; Paweł Stączek; Piotr Wolszczak (Communications - Scientific letters of the University of Zilina, 2021)
The automotive industry faces huge challenge in environmental protection by reducing fossil fuels and energy consumption by developing various practical solutions in energy harvesting. The current analysis is related to the diesel engine power supply system in a passenger off-road vehicle for application of the piezoelectric energy harvesting system. Experimental tests were carried out for the three constant rotational speed values - 800, 1000 and 1500 rpm. The results pertained to operational and simulation tests of available power supply options from the engine suspension system in the vehicle, e.g. to power sensors supervising the engine’s operation or other small electrical devices in the vehicle. The simulations of output voltage were conducted by means of a nonlinear model with a resonator coupled to a piezoelectric elastic beam deformed in the magnetic field to improve the band of frequency transducing kinetic mechanic energy into electric energy.